Inovação e o papel da cooperação universidade-empresa na obtenção de vantagens competitivas - Desidério, Paulo Henrique Martins (2016)
Technological innovation is perceived in the company as a strategy to achieve competitive advantage. Companies can adopt the innovative process as a strategy and internalize it in research and development areas. Another possibility is the external absorption of knowledge and inventions by universities, research centers, suppliers, strategic partners and other companies. In countries with high levels of competitiveness, mechanisms have been created to strengthen the ties of cooperation between research institutions and companies. In Brazil perceives an intensity of technology-based research in science and technology institutions, behavior that is not reflected in business organizations. Therefore, this thesis questioned whether the university-business cooperation exercises influence in the business competitive advantage. For this context, the objective was to verify the role of university-industry cooperation in generating competitive advantage of companies. Thus, this thesis verified the practices of university-business cooperation between the managers of innovation of science and technology institutions and companies, the competitive advantages that companies get this relationship through the PIP model (Product Innovation Performance), the types of innovation identified by managers of innovation and companies and the contributing factors and inhibit the process of university-industry cooperation. As methodological north, this research was descriptive guidance by use of mixed methods approach, with a qualitative search of categories linked to innovation, university-industry cooperation, competitive advantage and technology transfer. In sequence, realized the construction of the scales by categories identified in the literature and the qualitative phase, for further quantitative collection through a questionnaire applied in managers of innovation linked to FORTEC Forum and the companies associated with technology parks and incubators affiliated of ANPROTEC and ANPEI that demand technological innovation, with subsequent analysis of the data by means of structural equation modeling in the method of partial least squares. The results showed a positive correlation between university-industry cooperation and competitive advantage in product innovation in companies by means of interaction with the university for technology transfer. Were also identified fourteen categories drawn from interviews with managers of innovation and distributed in five metacategories related to structures, processes, interaction.